Harvest Anticipation, Yield and Economic Feasibility of Wheat by Application of Non-Selective Herbicides - Fipke, Glauber Monçon; Cunha, Vinicius dos Santos; Deak, Evandro Ademir; Stecca, Jessica Deolinda Leivas; Pires, João Leonardo Fernandes; Arismendi, Guilherme de Almeida; Grün, Eduarda; Martin, Thomas Newton (Journal of Agricultural Studies, 2021)
The present work aims to evaluate the possibility of anticipating the wheat harvest by the application of non-selective herbicides in the pre-harvest conditions, thereby providing productive and economic viability. In total, 13 treatments were executed, which includes the spraying of different herbicide combinations (glufosinate-ammonium, glyphosate, and paraquat) in the phenological stages (Z-83, Z-85, Z-87, Z-92), and treatments without application of herbicides. Further, the treatment step was followed by providing different harvest conditions such as (i) glufosinate-ammonium: 9.5 and 8.8 days, (ii) glyphosate: 11.2 and 10.9 days, and (iii) paraquat: 7.9 and 8.5, where the first numerical value corresponds to number of days for the year 2016 followed by 2017. A mean reduction in seed yield of 4.6 % (BRS Parrudo) and 25.4 % (TBIO Sinuelo) was observed upon application of herbicides in the first two phenological stages. Additionally, an economic loss reaching up to R 2512 ha-1, was demonstrated. Therefore, the application of the non-selective herbicides glufosinate-ammonium and paraquat in the pre-harvest results in wheat phytointoxication, however, promoting harvest anticipation in 4.8 and 5.3 days, respectively.